2021
DOI: 10.2196/26509
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Record Portal Use by Family Caregivers of Patients Undergoing Hematopoietic Cell Transplantation: United States National Survey Study

Abstract: Background As family caregivers of patients undergoing hematopoietic cell transplantation have multifaceted caregiving responsibilities (such as medical, household, financial) of long duration, they also have multiple physical, social, psychological, and informational needs. Objective This study explored the prevalence of electronic health record patient portal use by family caregivers for managing both their own and their hematopoietic cell transplanta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
14
1
2
Order By: Relevance
“…Our finding that caregivers with depression were less likely to use their care recipient’s portal was in contrast with other recent research that finds the opposite relationship [ 32 ]. Although it is possible that the use of the care recipient’s patient portal is a way of gathering information if the depression is related to caregiving or that using the portal actually facilitates social engagement by enabling the caregiver to communicate with information or with the health care system, it is also possible that the use of a care recipient’s patient portal could actually exacerbate depression or anxiety—an area requiring further study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that caregivers with depression were less likely to use their care recipient’s portal was in contrast with other recent research that finds the opposite relationship [ 32 ]. Although it is possible that the use of the care recipient’s patient portal is a way of gathering information if the depression is related to caregiving or that using the portal actually facilitates social engagement by enabling the caregiver to communicate with information or with the health care system, it is also possible that the use of a care recipient’s patient portal could actually exacerbate depression or anxiety—an area requiring further study.…”
Section: Discussioncontrasting
confidence: 99%
“…We report findings from our National Caregiver Health Survey, 30 , 31 which is part of a larger, multi-phase project. 19 , 30 , 32 40 The survey was implemented by the Center for Survey Research at Indiana University (LY).…”
Section: Methodsmentioning
confidence: 99%
“…We used a subset of 16 items from the 28-item Brief COPE, which assesses the self-reported frequency of use of 14 different coping strategies to deal with a particular situationally specific life event (in this case, self-care and caregiving for a person undergoing HCT), including self-distraction, active coping, denial, alcohol and drug use, use of emotional support, use of instrumental support, behavioral disengagement, venting, positive framing, planning the use of humor, acceptance, and religion. 31 , 43 We used exploratory factor analysis to reduce the 16 items into a smaller set of factors. Based upon a scree plot, we found that four factors were sufficient, with eigenvalues of 1.85, 1.52, 1.23, 0.83, and 34% of total variance explained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(45,45%), são do ano de 2020 13,14,[16][17][18] , seguido do ano de 2021 com 2 (18,18%) das publicações 15,19 18,20 .…”
Section: Resultsunclassified